„Sumienie” w dziejach polszczyzny - Miodek, Jan (Horyzonty Wychowania, 2017)
The article quotes the definitions of sumienie (conscience) found in general dictionaries of Polish language, in specialist dictionaries – ethical, theological as well as in journalistic texts and scientific texts for the general public. In all of these studies, the concept comes down to the ability to judge one’s own conduct, sense of responsibility for this, differentiating between good and evil, and especially realizing the harm you did to another man. Such comprehension leads to the etymology of sumienie, that is the Latin form conscientia, which literally means „being, communing with the knowledge about oneself”, which has been functioning up till the present day as the word form conscience in English and French. Polish original form of this word – sąmnienie – is a calque (replica), i.e. a literal translation, of the Latin word. For a very long time there were tonal variants functioning in our language, e.g. sumnienie, samnienie, somnienie, sampnienie. The form sumnienie lasted the longest, namely until the 19thcentury. Escape from the north Polish phonetic realization of the combination mi as mń, being a manifestation of exaggerated linguistic correctness (hypercorrectness) has led to the final establishment of the only form possible – sumienie – nowadays.